Bioprospecting of Chitinolytic Diazotroph Rhizospheric Bacterial Isolated From Mucuna bracteata as Biocontrol Against Ganoderma boninense - Yurnaliza (International Journal of Ecophysiology, 2021)
Ganoderma boninense is an infectious phytopathogenic fungus of basal stem rot in oil palm with the need of significant biocontrol strategy or alternative. Bioprospecting of chitinolytic diazotroph bacteria from rhizosphere of Mucuna bracteata as Legume Crop Cover (LCC) in oil palm plantations is potential to investigated. The aims of this study were to obtain total population of diazotroph bacteria and chitinolytic diazotroph bacteria, to evaluate its antagonistic properties followed by identification of the isolate based on 16S rRNA gene encoding. Diazotroph bacteria were isolated from M. bracteata rhizosphere originating from three oil palm plantations (PTPN III, PTPN IV unit Adolina Medan, and Perkebunan rakyat Simalingkar), followed with chitinolytic assay, morphological characterization, antagonistic assay against G. boninense, lytic assay of G. boninense mycelium by using crude chitinase and molecular identification of potential isolate. Total population of diazotroph bacteria in M. bracteata rhizosphere ranged between 2.80–3.83 × 106 CFU/g. Screening of chitinolytic diazotrophs using colloidal chitin medium obtained 23 bacterial isolates and 14 of them were known as antagonists to G. boninense. Five isolates with the highest anti Ganoderma were DK17 (71,15%), DK10 (69,70%), DK07 (59,63%), DK21 (53,48%), and DK19 (52,0%). The highe1st lytic activity of crude chitinase to G. boninense mycelium was produced by DK17. Molecular identification of five potential isolates revealed different identities, e.g. Enterobacter aerogenes (DK07), Mycobacterium senegalense (DK10), Bulkhoderia cepacia (DK17), Pseudomonas stutzeri (DK19), and Bulkhoderia cepacia (DK21). Based on these results, chitinolytic diazotroph bacteria isolated from M. bracteata rhizosphere were able to control G. boninense